A Pulse on Language Equity in First-Grade Urban Classrooms - (:unkn) unknown (My University, 2021)
Students of color are the majority in many U.S. urban public schools, yet U.S. education policy and practice continue to be centered largely on White, middle-class, monocultural, and monolingual norms of educational achievement (Alim & Paris, 2017). The purpose of this phenomenological study was to learn more about the teacher decision-making process and the extent to which first-grade mainstream teachers include culturally and linguistically sustaining practices during literacy instruction. Evidence using the foundations of the critically conscious teacher framework (Joseph & Evans, 2018) and of the role of language and culture as a medium in teaching and learning (de Jong & Harper, 2008) were used to analyze the progress in teacher development and practice during literacy instruction. Three findings emerged from the data: (a) Teacher decision making was oriented in a variety of self-selected professional growth experiences; (b) Teachers leveraged the online setting to enhance a culturally sustaining learning environment; (c) Teachers sought validation for decision making in their work with culturally sustaining practices. The findings of this study inspired the development of the Teacher Habits of Culturally Sustaining Practice Model, which contributes to research focused on the education and support of teachers’ effective literacy practices in culturally and linguistically diverse classrooms.
Keywords: Equity; Languge; literacy; multilingualism; pluralism; pluralistic